A kolozsvári jezsuita iskola megnyitására kiadott tézisek (1581) - Lázár, István Dávid (Antikvitás & Reneszánsz, 2019)
In May 1581, the Jesuit College in Kolozsvár (Cluj) was opened in the presence of Prince Báthori Kristóf. The opening ceremony was scheduled to include a dispute between the Jesuits and the Protestants, for which the theses compiled by Wolfgang Schreck S.I. have been already printed, entitled: THESES DE PURO ET EXPRESSO DEI VERBO, tam scriptis, quam viva voce tradito, et pari utriusque autoritate, necessitate, utilitate ac fine. According to contemporary reports, the Protestants did not stand up to the debate, so the Jesuit brothers disputed among themselves. A few years later, however, a response came from a Protestant, Péter Laskai Csókás, which was printed in 1585 in Geneva with the title Theorematum de puro et expresso Deo verbo… examen et refutatio. Only one copy of the Theses has survived, which is currently kept in the TelekiBolyai Library in Marosvásárhely (Târgu Mureş). After a brief introduction, I present the Latin text of the paper that has been ignored by the research so far.